2010
DOI: 10.1002/chem.201000637
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Fluorescent Boronic Acids That Have Extraordinarily High Affinities for Diols in Aqueous Solution at Physiological pH

Abstract: The boronic acid group is an important recognition moiety for sensor design. Herein we report a series of isoquinolinylboronic acids that have extraordinarily high affinities for diol-containing compounds at physiological p H. In addition, 5- and 8-isoquinolinylboronic acids also showed fairly high binding affinities with d-glucose (Ka = 42 and 46 M−1, respectively). For the very first time, weak but encouraging binding with cis-cyclohexanediol was found for these boronic acids. Such binding was coupled with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…This observed trend in k on is the same as the thermodynamic binding constants as described previously. 4 The various factors that affect the binding affinity between a boronic acid and a diol have been discussed elsewhere. 7, 8 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This observed trend in k on is the same as the thermodynamic binding constants as described previously. 4 The various factors that affect the binding affinity between a boronic acid and a diol have been discussed elsewhere. 7, 8 …”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it is interesting that 4-IQBA showed fluorescent intensity decreased upon binding with D-glucose in the stopped-flow instrument, while we observed fluorescent intensity increased in the binding study using the fluorometer as reported before. 4 One possible reason is again associated with the structural change of the complex. It is possible that the species observed in the stopped-flow experiments was in the pyranose form, while the thermodynamic experiments observed the furanose form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar reports were identified with regard to 3‐amino phenylboronic acid compound and has shown interactions with mono and disaccharides and suggested fluorescence quenching by forming esters with sugars showing relatively more predominance for fructose . Likewise, isoquinolinylboronic acids were proven to show good binding properties with glucose and had binding affinity in the range 42–46 M −1 . Naphthalene based fluorescent boronic acid showed 41‐fold enhancement of fluorescence intensity upon binding fructose at pH 7.4 .…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to understand how those factors affect the thermodynamics of the dynamic bond have focused on maximizing the binding affinity (Keq) at physiological pH. 9,42,[44][45][46][47][48][49] In particular, those studies have introduced new classes of boronic acids with high binding affinities, such as Wulff-type boronic acid and benzoxaborole. 9,44,50 In contrast, studies investigating the kinetics of this dynamic reaction are largely motivated by boronic acid-based receptors and sensors, and thus rely on specific model diols to elucidate the speciation and pathways of the complex mechanism (see Electronic Supplementary Information (ESI), Table S1).…”
Section: Introductionmentioning
confidence: 99%